Relationship Between Investment and Cash Flow Under High and Low Investment Opportunities: Evidence from Pakistani Manufacturing Firms (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
This paper examines the relationship between cash flow and investment under high and low investment opportunities of 167 Pakistani non-financial manufacturing firms listed in the Karachi Stock Exchange during the period 2004-2013. Tobins Q is employed to capture the investment opportunities and sales are taken as control variable.  A panel regression model is used to investigate the relationship of cash flow, Tobins Q and sales on investment.  In case of high investment opportunities firms, the relationship of investment and cash flow is positive and significant while under low investment opportunities firms, this relationship is also positive but insignificant.  These results indicate that the high opportunities firms rely mostly on internally generated cash flow whereas the low investment opportunities firms prefer to distribute its earnings as dividend.